Sharia Compliant: A User's Guide to Hacking Islamic Law: by Rumee Ahmed, Stanford, Stanford UP, 2018, 247 pp., $22.00 (paperback), ISBN 978-1-5036-0570-1. - Hartshorn, Ian M. (Terrorism & Political Violence, 2021)
Rumee Ahmed offers a lively and readable account of how Islamic law can (and in the assessment of some, should) be changed, adapted, and reformed. Ahmed offers, as the subtitle suggests, a handbook for practitioners who are interested in what he calls "hacking" Islamic law. The book does not contain a sustained empirical argument, instead Ahmed offers a normative one, that Muslims should seize the means of revising Islamic law for themselves, and that doing so is not only a modern necessity, but a long-standing civilizational effort.